Parental participation in the educational management of the Nadi Municipal Child Development Center, Nadi Subdistrict Municipality, Samut Sakhon Province - Deekajang, Saowanee; Thewapitak, Bunthida; Dejbamrung, Sombat; Dejbamrung, Somchai (Journal for Developing the Social and Community, 2026)
Background and Aims: Parental involvement in the management of education at child development centers plays a crucial role in children’s development, as it fosters collaboration between the home and the center to ensure effective learning that meets the individual needs of each child. The purpose of this research is to study 1) the participation of parents in the education management of the Nadi Municipal Child Development Center under Nadi Subdistrict Municipality, Samut Sakhon Province 2) Guidelines for the development of parents' participation in education management of the Nadi Municipality Child Development Center under Nadi Subdistrict Municipality Samut Sakhon Province. Methodology: This study was descriptive research. The population used in this study is 90 parents of Nadi Municipal Child Development Center under Nadi Subdistrict Municipality. The research tools used include opinion questionnaires and structured interviews. Statistics used in data analysis include frequency, percentage, average, standard deviation and content analysis. Results: 1) The participation of parents in the education management of the Nadi Municipal Child Development Center under Nadi Subdistrict Municipality, Samut Sakhon Province Overall, the level of parental participation was found to be very high. When considering each aspect, it was found that the aspect with the highest average is the decision-making aspect has the highest average, followed by parenting, and the aspect with the lowest average is participation. 2) Guidelines for the development of parental participation in the educational management of the Child Development Center, Nadi Municipality under the Municipality of Nadi Subdistrict, Samut Sakhon Province. There are many guidelines as follows: 1) Parents teach children to take a shower and clean their bodies on a daily basis, especially after playing or doing activities that make the body dirty. 2) Inform information on online channels such as websites, applications or social media groups for communication with parents. 3) Organize activities that give parents the opportunity to show their talents, such as teaching cooking or storytelling. 4) Parents for children to participate in arranging outdoor space according to their interests. Take care of self-grown trees to give children the opportunity to think, choose, and make independent decisions. 5) Building a network to promote cooperation between parents and between parents and teachers/teachers 6) Organize activities that give parents the opportunity to meet and talk informally, such as graduation parties, children's, children's or various parties. Conclusion: Parents play an essential role in the development of children’s learning and behavior, particularly through their involvement in decision-making and caregiving, which are key factors in ensuring proper care both inside and outside the center. In addition, the strategies for enhancing parental involvement identified in the study include promoting children’s hygiene habits, utilizing online communication channels, organizing activities that allow parents to participate and showcase their skills, building collaborative networks between parents and teachers, and arranging informal gatherings. All of these highlight the importance of cooperation between families and child development centers for the holistic development of children and represent approaches that should be continuously encouraged to ensure the best outcomes for children in the future.